2002
DOI: 10.3354/meps241013
|View full text |Cite
|
Sign up to set email alerts
|

Fate of cyanobacterial toxins in the pelagic food web: transfer to copepods or to faecal pellets?

Abstract: Toxic cyanobacterial blooms are a common phenomenon in the Baltic Sea. The fate of the toxin in the food web is largely unknown. We studied the effect of algal diets on production of pellets and toxin content of the calanoid copepod Eurytemora affinis in the northern Baltic Sea. Fieldcollected copepods were fed with (1) cultured toxic cyanobacteria Nodularia spumigena; (2) cultured non-toxic flagellates Brachiomonas submarina; and (3) a natural phytoplankton assemblage. Natural phytoplankton was dominated by n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
1
2

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 58 publications
2
26
1
2
Order By: Relevance
“…Values found in E. affi-nis were in the same range as previously observed for this species , Lehtiniemi et al 2002.…”
Section: Toxin Accumulationsupporting
confidence: 78%
See 3 more Smart Citations
“…Values found in E. affi-nis were in the same range as previously observed for this species , Lehtiniemi et al 2002.…”
Section: Toxin Accumulationsupporting
confidence: 78%
“…Addition of B. submarina to <100 µm FW increased the C (carbon) and N (nitrogen) contents of Eurytemora affinis eggs even when no increase was detected in the females (Koski 1999). Furthermore, we have observed that the pellet production rate by E. affinis feeding on B. submarina, which corresponded to rates of other copepods feeding on good food, was significantly higher than on natural community or N. spumigena diets (Lehtiniemi et al 2002).…”
Section: Feeding and Reproductionmentioning
confidence: 52%
See 2 more Smart Citations
“…N. spumigena cells can also be ingested by herbivorous zooplankton. This was definitely proved in experiments with radiolabeled NOD and by detection of the toxin in faecal pellets produced by the organisms (Lehtiniemi et al, 2002;Karjalainen et al, 2003Karjalainen et al, , 2005. Zooplankton is presumed to be an important vector in toxin transfer to higher trophic levels.…”
Section: Introductionmentioning
confidence: 79%